Topical administration of 5-aminosalicylic acid enemas in patients with ulcerative colitis. Studies on rectal absorption and excretion. Issue 4 (April 1985) - Campieri, M; Lanfranchi, G A; Boschi, S; Brignola, C; Bazzocchi, G; Gionchetti, P; Minguzzi, M R; Belluzzi, A; Labò, G
Abstract : 5-aminosalicylic acid (5-ASA) is a new treatment for patients suffering from ulcerative colitis but only limited information is available about its rectal absorption. We therefore studied seven patients with ulcerative colitis in remission, and five with active disease to determine acetylated and free 5-ASA plasma concentrations and urinary acetyl 5-ASA after the administration of three different types of enemas: (2 g 5-ASA/100 ml, 4 g/100 ml, and 200 ml). In patients in remission urinary acetyl 5-ASA excretion was dose and volume dependent (p less than 0.01; p less than 0.05) but this correlation was absent in active disease. Because aminosalicylates are usually eliminated through the kidney, these low values (10% in active disease and 19% in those in remission) suggest that the beneficial action may be local. Urinary recovery was significantly lower in patients with active disease (p less than 0.01; p less than 0.02). No accumulation of 5-ASA was found in plasma after repeated daily administration.